Analysis of soil characteristics and microclimate based on smart sensor systems - Risnatati; Yasiva Dortiana Lima; Muhammad Musyaddad; Winny Liliawati (Journal of Character and Environment, 2026)
Background: Soil and microclimatic conditions play important roles in regulating ecosystem processes in tropical forest environments. However, information regarding these environmental characteristics in Tahura Ir. H. Djuanda based on smart sensor measurements remains limited. This study aimed to characterize soil and microclimatic conditions in the conservation area using a smart sensing approach. Methods: A quantitative descriptive field study was conducted in April 2026 at three observation points in Tahura Ir. H. Djuanda, West Java, Indonesia. Environmental parameters were measured using a 6-in-1 Intelligent Soil Tester (Model ST03). The observed variables included soil moisture, soil fertility, soil pH, soil temperature, light intensity, and air humidity. Data were analyzed descriptively through comparison and interpretation of measurements across observation points. Findings: Soil moisture remained consistently high (99%) at all observation points. Soil fertility ranged from 209 to 582 μS/cm, while soil pH varied between 6.5 and 7.0, indicating slightly acidic to neutral conditions. Soil temperature increased from 21.6°C to 26.0°C, light intensity ranged from 628 to 1,304 lux, and air humidity varied from 78% to 84%. These results indicate spatial variability in environmental parameters while maintaining conditions typical of tropical forest ecosystems. Conclusion: Tahura Ir. H. Djuanda exhibits favorable soil and microclimatic conditions characterized by high soil moisture, relatively fertile soils, near-neutral pH, warm soil temperatures, low understory light intensity, and high atmospheric humidity. These conditions support ecological processes and vegetation growth within the conservation area. Novelty/Originality of this article: This study provides baseline information on soil and microclimatic conditions in Tahura Ir. H. Djuanda using a smart sensor-based approach that supports future environmental monitoring and conservation management.